2015
DOI: 10.1080/19443994.2014.951966
|View full text |Cite
|
Sign up to set email alerts
|

Co-removal of phosphorus and nitrogen with commercial 201 × 7 anion exchange resin during tertiary treatment of WWTP effluent and phosphate recovery

Abstract: 2014): Co-removal of phosphorus and nitrogen with commercial 201 × 7 anion exchange resin during tertiary treatment of WWTP effluent and phosphate recovery, Desalination and Water Treatment, A B S T R A C TExcessive nitrogen and phosphorus discharge into natural water from wastewater treatment plants still have the potential of causing eutrophication. How to remove those excessive nitrogen and phosphorus in an appropriate way is welcome in practice. This study co-removed nitrate and phosphorus via the operatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…Moreover, as the experimental work of this study indicated, passing effluent from the Purolite column through the HFO column removed almost all phosphate and the series column set up removed both nitrate and phosphate from wastewater (Das Gupta et al 2012). Another commercial 201 Â 7 exchange resin column was used for the simultaneous removal of nitrate and phosphate from aqueous solution (Wei et al 2015). Experimental results indicated a maximum nitrate and phosphate adsorption capacity of 107.59 and 12.47 mg/g, respectively.…”
Section: Novel Miscellaneous Adsorbentsmentioning
confidence: 73%
See 1 more Smart Citation
“…Moreover, as the experimental work of this study indicated, passing effluent from the Purolite column through the HFO column removed almost all phosphate and the series column set up removed both nitrate and phosphate from wastewater (Das Gupta et al 2012). Another commercial 201 Â 7 exchange resin column was used for the simultaneous removal of nitrate and phosphate from aqueous solution (Wei et al 2015). Experimental results indicated a maximum nitrate and phosphate adsorption capacity of 107.59 and 12.47 mg/g, respectively.…”
Section: Novel Miscellaneous Adsorbentsmentioning
confidence: 73%
“…The selected eluent needs to be non-interacting with the surface of the adsorbent during the repeated use (the adsorbent should be insoluble and not have surface interaction with the eluent). Different concentrations of HCl (Rezaei Kalantary et al 2016;Song et al 2016); H 2 SO 4 (Lee et al 2018); NaOH (Chatterjee & Woo 2009;Xie et al 2014;Drenkova-Tuhtan et al 2017;Rashidi Nodeh et al 2017;Wu et al 2017;Jiang et al 2018;Liao et al 2018;Pham et al 2019;Shi et al 2019;Alagha et al 2020;Sereshti et al 2020); NaCl-NaOH binary solution (Zhang et al 2016;Banu & Meenakshi 2017;Qiu et al 2017), NaCl (Wei et al 2015;Liu et al 2019aLiu et al , 2019b; citric acid (Jiang et al 2017a(Jiang et al , 2017b, and Na 2 CO 3 (Anirudhan et al 2012) were used as nitrate and phosphate leaching agent from their adsorbents. Basic solution interferes with the pH driven electrostatic interaction between nitrate and phosphate ions and metal cation (Rashidi Nodeh et al 2017;Liao et al 2018;Sereshti et al 2020).…”
Section: Nitrate and Phosphate Recoverymentioning
confidence: 99%
“…To decide which model should be considered as the most appropriate, Elovich model, which indicates the role of heterogeneity of the adsorbent surface and also supports chemisorption as possible mechanism of sorption, was fitted on the kinetic data. As can be seen, the values of R 2 for Elovich model are high (0.9122 and 0.9314), and this indicates chemisorption as possible mechanism of sorption (Liu et al 2013;Sowmya and Meenakshi 2014;Wei et al 2015).…”
Section: Adsorption Kineticsmentioning
confidence: 86%
“…The most investigated sorbents for their performances in phosphate removal could be grouped in (1) biomass-derived sorbents (Karthikeyan et al 2019;Wilson 2016, 2017), (2) inorganic oxides (Hao et al 2019;Jing et al 2020;Liu et al 2011;Wu et al 2019), (3) composite sorbents (Dragan et al 2019;Du et al 2020;Jia et al 2020;Li et al 2019;Liao et al 2020;Luo et al 2018Luo et al , 2019Rashid et al 2017;Wan et al 2017;Zong et al 2018), and (4) ion exchangers (Ding et al 2012;Liao et al 2020;Liu et al 2013; Responsible Editor: Tito Roberto Cadaval Jr Sowmya and Meenakshi 2014;Wei et al 2015;Zarrabi et al 2014;Zhu et al 2017). Various ion exchangers have been evaluated for their sorption capacity of phosphate, either alone (Ding et al 2012;Liao et al 2020;Liu et al 2013;Sowmya and Meenakshi 2014;Wei et al 2015;Zarrabi et al 2014) or as hybrids with metal salts (Zhu et al 2017). It has been reported that strong base anion exchangers (SBAEx) constitute a convenient alternative for phosphate adsorption/ recovery (Ding et al 2012;Sowmya and Meenakshi 2014;Wei et al 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation